Circulating miRNAs as intercellular messengers, potential biomarkers and therapeutic targets for Type 2 diabetes. (June 2015) - Mirra, Paola; Raciti, Gregory Alexander; Nigro, Cecilia; Fiory, Francesca; D'Esposito, Vittoria; Formisano, Pietro; Beguinot, Francesco; Miele, Claudia
MiRNAs have emerged as key epigenetic regulators of metabolism. Their deregulation contributes to metabolic abnormalities, proposing their potential role as therapeutic targets for Type 2 diabetes. The exciting finding that miRNAs exist in the bloodstream suggests that circulating miRNAs may act in a hormone-like fashion. Despite the fact that significant progress has been made in understanding circulating miRNAs, this topic is full of complexities and many questions remain unanswered. The goal of this review is to bring together up-to-date knowledge about circulating miRNAs and their role as intercellular communicators as well as potential biomarkers and therapeutic targets in metabolic diseases, providing examples of possible clinical applications for circulating miRNAs in diabetes and cardiovascular complications.